Onomastics of the Village Velika Kruševica near Rekovac - Jašović, Golub (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The paper presents the onomastics recorded in Levač village Velika Kruševica which is situated in the Levač municipality. We have registered toponyms, personal and family nicknames, personal names and surnames of all the residents who have been in the village during our visit (some have been working in the fields). A short analysis of lexical and semantic units has been done as well as the classification of the registered onyms. Integral part of the paper is also a dictionary with an alphabetical list of the recorded onyms.